The Problem of Genesis of Seyyids’ Institutes in the Post-Golden Horde Turkо-Tatar States » - D.M. Iskhakov (Золотоордынское обозрение)
The article analyzes an insufficiently investigated problem of the formation of seyyids’ institute within the Turkic-Tatar States of the 15th–16th centuries, which were the historical heirs of the ulus of Jochi (Golden Horde). The author found that this institution was characteristic for all, without exception, Turkic-Tatar state formations that emerged after the collapse of the Golden Horde. A number of features of this institution (existence of family relationship between the seyyids’ “houses” of different Tatar yurts, seyyids’ participation not only in the diplomatic and administrative affairs but also in military actions) indicates that it appeared in the period of the ulus of Jochi, more precisely, during the reign of khan Uzbek who had completed Islamization of this State. As a result of the study of the complex issues related to the seyyids who lived in the Turko-Tatar khanates and hordes, the author concluded that there was a link between them and the lineages of the Golden Horde seyyids affiliated with the Yasaviyya tariqa. Overall, the author both emphasizes the apparent Golden Horde origin of this very important social institution functioned in all the Turkic-Tatar state formations and indicates the presence of real contacts (including gentilitial ones) between the seyyids’ branches located in different States.